2020
DOI: 10.1002/jmv.26353
|View full text |Cite
|
Sign up to set email alerts
|

The dynamic changes of serum IgM and IgG against SARS‐CoV‐2 in patients with COVID‐19

Abstract: Coronavirus disease 2019 (COVID‐19) caused by severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) has become a worldwide pandemic since it emerged in December, 2019. Previous studies have reported rapid antibody response to SARS‐CoV‐2 with the first 2‐3 weeks after symptom onset. Here, we retrospectively described the dynamic changes of serum IgM and IgG specifically against SARS‐CoV‐2 in later weeks (mainly 4‐10 weeks) in 97 hospitalized patients with COVID‐19. We observed that serum IgM and IgG, esp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
70
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
4
2

Relationship

1
9

Authors

Journals

citations
Cited by 78 publications
(76 citation statements)
references
References 25 publications
(55 reference statements)
5
70
1
Order By: Relevance
“…In addition to a signi cant decrease in the level of the in ammatory factor CRP, KL-6, an indicator of pulmonary brosis, was also signi cantly reduced. In addition, all three antibodies speci c to SARS-CoV-2, IgA, IgM, and IgG, were very signi cantly down-regulated, consistent with the results reported in previous studies [14,26]. It is worth investigating whether recovered patients will have the same risk of infection as that of previously uninfected people when encountering the SARS-CoV-2 virus again [26].…”
Section: Discussionsupporting
confidence: 87%
“…In addition to a signi cant decrease in the level of the in ammatory factor CRP, KL-6, an indicator of pulmonary brosis, was also signi cantly reduced. In addition, all three antibodies speci c to SARS-CoV-2, IgA, IgM, and IgG, were very signi cantly down-regulated, consistent with the results reported in previous studies [14,26]. It is worth investigating whether recovered patients will have the same risk of infection as that of previously uninfected people when encountering the SARS-CoV-2 virus again [26].…”
Section: Discussionsupporting
confidence: 87%
“…It has been shown in several studies that SARS-CoV-2 antibody response appears earlier and is more pronounced in severely ill patients compared to less severe cases [11,12]. In addition, the kinetics of antibody decline may differ as recent studies suggest individual variation in antibody decline [13]. These factors may influence the test results of different serological assays and could not be systematically considered in our study since the severity of disease in the COVID-19 patients was not known apart from the fact that all patients were treated as outpatients.…”
Section: Resultsmentioning
confidence: 99%
“…In a breakthrough report, Ibarrondo et al described that SARS-CoV-2 IgG antibodies decayed early and rapidly after symptom onset in persons with mild disease [14]. Other studies confirmed that indeed there is a decay in IgG levels but at a slower rate and at later times than that reported by Ibarrondo et al [11, 15-21]. Although our understanding in the antibody dynamics is still incomplete, specific IgG levels appear to be maintained during 4-5 months, or even longer, if we consider our data from plasma non-donors, presented in figure 5A.…”
Section: Discussionmentioning
confidence: 97%